Vulnerability Analysis of a Mutual Authentication Protocol Conforming to EPC Class-1 Generation-2 Standard - Mu’awya Naser; Rahmat Budiarto; Ismat Aldmour; Pedro Peris Lopez (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In this paper we scrutinize the security properties of an RFID authentication protocol conforming to the EPC Class-1 Generation-2 standard. The protocol is suitable for Gen-2 passive tags and requires simple computations. The authors claim that the scheme provides privacy protection and authentication and offers resistant against commonly assumed attacks. We propose a de-synchronization and an impersonation attack in which the disclosing of the secret information (i.e. secret key and static identifier) shared between the tag and the reader is unnecessary to success in these attacks.